PREVALENCE OF HELICOBACTER PYLORI IN OBESE PATIENT - Altaee, Mohammed J.; Mohammed, Bilal; Jasim, Ahmed S.; Abdulkadhm, Hasanin (Journal of Global Pharma Technology, 2024)
Background: Helicobacter pylori is a widely recognized pathogen that exhibits a high prevalence among the global population. The infection caused by H. pylori poses significant health risks due to its association with various gastrointestinal disorders, including gastric ulcers, duodenal ulcers, chronic gastritis, and gastric carcinoma. The regulation of gastric hormones, such as ghrelin and leptin, plays a crucial role in energy homeostasis. Ghrelin, secreted by P/D1 cells in the stomach during periods of hunger, stimulates appetite and promotes food consumption. Conversely, leptin, released by P cells in the stomach and adipocytes after food intake, reduces appetite and fosters a sense of fullness. Individuals infected with H. pylori tend to have lower plasma levels of both ghrelin and leptin compared to those who are not infected. Consequently, the reduced serum leptin levels can delay the sensation of satiety during meals, leading to increased energy intake and a potential development of obesity. Aim: Our study has been proposed and structured to achieve the below objectives: Prevalence of H. pylori associated with overweight. Presence or absence of some clinical signs among patient. Prevalence of infection among age group. Methods: Blood seem were collected from 30 person during the period from February to April 2023 and both gender were participate in this study with age ranging from 20-50 years old.Blood tests were used to measure the antibodies against H pylori. The sample were collected and small amount of it applied in to well In the test line area, anti-human IgG is rendered immobile. Following its addition to the device's specimen well, the specimen reacts with the test's H. pylori antigen-coated particles. This mixture interacts with the immobilized anti-human IgG and migrates chromatographically over the course of the test. A colored line will show up in the test line region, signifying a positive result, if the samples contain H. pylori antibodies. A colored line indicating a negative result won't show up in this area if the specimen is devoid of H. pylori antibodies. To act as a methodical. Result: Our study shows that Middle age group were the highest percentage among other age group (35 %). In another hand the overweight patient suffering from H. pylori infection constitutes about 36.7 %. Keywords: Helicobacter Pylori, Obese Patient, Infection.